Nilai Edukatif Tradisi Peringatan Hari Kematian di Kenagarian Manggopoh, Sumatra Barat - Irsyadul Ubad; Silfia Hanani; Iswantir M. (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2020)
The Nagari Manggopoh community has a tradition of commemorating the day of one's death which takes place on the third, seventh, fourteenth, fortieth, hundredth, and thousandth days, but the community does not yet understand the educational values. The focus of the research is educative values in the tradition of commemorating the day of death, and their implications for strengthening Minangkabau traditional values. The object of this research is the Islamic community in Nagari Manggopoh that carries out a tradition of commemorating one's death by analyzing the educational values contained in it. The population in this study is the community who carry out the tradition of the commemoration of death. Data collection techniques are observation and interviews, then analyzed using qualitative analysis techniques, with inductive, deductive, and descriptive methods. The results of this research showed that there were some educative values contained in the tradition, namely sociological, cultural and cultural educational values, historical, and leadership.